An evaluation of Meriden Adventure Playground: Focus on impact on physical activity and healthy eating. (15th May 2017) - Price, Nikita; Trout, Alison
Abstract : This evaluation aimed to explore the impact of Meriden Adventure Playground (within North Solihull) on children's physical activity levels and healthy eating. A predominantly qualitative approach was taken throughout the evaluation using focus groups, interviews and questionnaires to collect data from 64 children, parents/guardians and playwork practitioners. Data from Fitbit activity trackers was gathered to measure calorie expenditure, steps, sleeping patterns and distance walked. An analytical, but descriptive, form of interpretative phenomenological analysis (IPA) was performed on the qualitative data. The main themes reported were: (1) freedom to initiate various types of play; (2) social interaction for parents/guardians and children; and (3) increased physical activity. Data from the activity trackers showed that the playground initiated increased levels of physical activity, including walking further and higher calorie expenditure. These findings suggest that the playground serves multiple positive functions that improve health and wellbeing for the community – primarily, increased physical activity for children and freedom of play.